2019
DOI: 10.1029/2018gl081821
|View full text |Cite
|
Sign up to set email alerts
|

Diurnally Migrating Lunar Water: Evidence From Ultraviolet Data

Abstract: Data from the Lunar Reconnaissance Orbiter Lyman Alpha Mapping Project and Diviner are consistent with surface water on the Moon varying in abundance with both terrain type and local time/temperature. A thermal desorption model including latitudinally varying desorption activation energy reproduces the observations. We interpret the observed variability in spectral slopes as water molecules in the uppermost lunar regolith (<1% of a monolayer) thermally adsorbing and desorbing from grains depending upon the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
77
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 35 publications
9
77
0
Order By: Relevance
“…At Reiner Gamma, the field strength is comparable to Gerasimovich, yet Reiner Gamma shows a weaker difference in water supression. We attribute this weaker difference due to the slightly lower latitude of Reiner Gamma (7°N vs 22°S), where warmer temperatures will reduce the background water (Benna et al, ; Farrell et al, ; Hendrix et al, ; Jones et al, ; Li & Milliken, ; Tucker et al, ; Wöhler, Grumpe, Berezhnoy, & Shevchenko, ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…At Reiner Gamma, the field strength is comparable to Gerasimovich, yet Reiner Gamma shows a weaker difference in water supression. We attribute this weaker difference due to the slightly lower latitude of Reiner Gamma (7°N vs 22°S), where warmer temperatures will reduce the background water (Benna et al, ; Farrell et al, ; Hendrix et al, ; Jones et al, ; Li & Milliken, ; Tucker et al, ; Wöhler, Grumpe, Berezhnoy, & Shevchenko, ).…”
Section: Discussionmentioning
confidence: 95%
“…Lunar surface water was then discovered with infrared data from spacecraft measurements (Clark, ; Pieters et al, ; Sunshine et al, ) and later on was confirmed with ground‐based telescope observations (Honniball et al, ); this water is stable in sunlight at middle to high latitudes (e.g., Clark, ; Honniball et al, ; Pieters et al, ; Sunshine et al, ). A major formation mechanism of this type of lunar surface water is attributed to solar wind implantation (Bandfield et al, ; Clark, ; Hendrix et al, ; Jones et al, ; Li & Milliken, ; McCord et al, ; Pieters et al, ; Sunshine et al, ; Tucker et al, ; Wöhler, Grumpe, Berezhnoy, & Shevchenko, ). Water was also directly observed in the Lunar Crater Observation and Sensing Satellite ejecta plumes at Cabeus crater (Colaprete et al, ; Gladstone et al, ; Hayne et al, ; Schultz et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data are a snapshot at one location and time on the Moon and so cannot address diurnal timescales or the timescales of the evolution of molecular water. Future 6 µm observations similar to UV observations 19 could constrain diurnal variations in molecular water across the lunar surface, and more extensive latitudinal and spatial coverage could also separate local geologic variations from general latitudinal trends.…”
mentioning
confidence: 87%
“…Poston et al 18 modelled the amount of molecular water that would be present on grain surfaces after several lunations and showed that only 3 µg g −1 of H 2 O can reside on the surface of grains at the derived brightness temperature, lunar time of day and latitudes of our observations (see Methods). Similarly, Hendrix et al 19 estimate that about 1% of a monolayer of molecular water is present if the diurnal variation in the UV water-ice band ratio is due to water, which corresponds to only a few µg g −1 of water. This almost certainly means that the water detected by SOFIA resides within the interior of lunar grains or is trapped between grains shielded from the harsh lunar environment, allowing it to survive a lunation.…”
mentioning
confidence: 96%